Leaf beetle diversity on a Southeast Asian continental island: Taxonomy, DNA barcoding, and preliminary evolutionary insights from Cat Ba Island, Vietnam - Dinh Thi Nguyen; Loan Thi Ho (PLoS ONE, 2026)
Continental shelf islands in Southeast Asia remain poorly studied with respect to insect diversity and evolutionary history. Here, we provide an integrative assessment of species diversity, DNA barcode variation, diversification dynamics, and historical biogeography of leaf beetles (Coleoptera: Chrysomelidae) on Cat Ba Island, northern Vietnam. Based on field surveys, 36 morphospecies operational taxonomic units (OTUs) belonging to 30 genera and five subfamilies were documented, with Galerucinae representing the most species-rich lineage. DNA barcoding of the mitochondrial COI gene generated 31 Barcode Index Numbers (BINs), most of which represent new records in the Barcode of Life Data System, highlighting substantial undocumented genetic diversity. COI-based analyses were further used to explore broad temporal and evolutionary patterns. Within this exploratory framework, divergence-time estimation under a relaxed molecular clock suggests that major lineages may have originated during the early–middle Miocene, predating the formation of the present-day island. Diversification analyses support relatively constant rates through time with low inferred extinction, consistent with expectations for continental shelf island systems shaped by repeated connectivity and isolation. Model-based biogeographic analyses indicate predominantly localized ancestral ranges, with Cat Ba Island and adjacent mainland regions playing recurrent roles in the assembly of the fauna. Together, these results provide baseline taxonomic and genetic data for a poorly known insular insect assemblage while offering a preliminary evolutionary context that should be interpreted with caution and that can serve as a foundation for future biodiversity monitoring and comparative studies in dynamic island–mainland systems.